The Influence of Critical Thinking and Student Engagement on Learning Outcomes in Gamification-Based Vocational Education - Baiaturridwan; Dedy Irfan; Resmi Darni; Muhammad Giatman (JTP - Jurnal Teknologi Pendidikan, 2026)
Vocational learning often faces challenges in fostering active student participation, particularly in practicum-based courses where more than 60% of students tend to be passively engaged during instructional activities, resulting in suboptimal learning outcomes. Therefore, an instructional approach that promotes active involvement is critically needed. This study aims to examine the role of critical thinking and student engagement in predicting learning outcomes within gamified vocational education, where gamification is positioned as a pedagogical approach rather than a statistical variable. This study employed a quantitative approach with an associative research design. The participants consisted of 22 students enrolled in a network programming practicum course, selected using a total sampling technique. Data were collected through Likert-scale questionnaires that met validity and reliability criteria (Cronbach’s Alpha ≥ 0.60). Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that critical thinking and engagement simultaneously have a significant effect on learning outcomes (p < 0.05), with a coefficient of determination (R² = 0.909), indicating a strong predictive model. Partially, engagement has a positive and significant effect on learning outcomes (p < 0.05), while critical thinking does not show a significant direct effect (p > 0.05), although it demonstrates a positive relationship. These findings suggest that the effectiveness of gamified vocational learning is more strongly influenced by student engagement as an active learning mechanism, rather than critical thinking as an independent factor.